The application of Life Cycle Assessment to achieve sustainable tourism: A literature review - Nofriya Nofriya; Barti Setiani Muntalif; Benno Rahardyan (Sustinere: Journal of Environment and Sustainability, 2022)
Increased development of tourism-related infrastructure to meet the needs of tourists visiting tourist destinations causes greater environmental problems such as greenhouse gas emissions, higher amount of waste, liquid waste as well as sanitation and aesthetics issues. Therefore, it is necessary to evaluate the environmental aspects of tourism activities using environmental performance indicators. The basic idea of the environmental performance evaluation framework is to identify and assess to facilitate continuous improvement and prevent further environmental degradation. The Life Cycle Assessment (LCA) can apply to find tourism activities that have negatively impacted environmental sustainability. Determination of environmental impacts using LCA is a method that can thoroughly identify the stages in tourism activities that can generate environmental impacts. LCA can find the amount of carbon footprint generated by tourism activities, the sector that has the most impact on the environment and the best alternative to realize sustainable tourism.